New sequence variants in patients affected by amyloidosis show transthyretin instability by isoelectric focusing - Hinderhofer, Katrin; Obermaier, Christian; Hegenbart, Ute; Schönland, Stefan; Seidler, Marc; Sommer-Ort, Iris; Barth, Ulrike (Amyloid, 2019)
The plasma protein transthyretin (TTR) can aggregate into insoluble amyloid fibrils causing systemic amyloidosis (ATTR amyloidosis) in patients carrying a variant TTR protein. If new variants arise, it is crucial to clarify whether they are disease-associated or benign. In this study, we further functionally characterize three new and unclassified TTR variants (Thr40Asn, Phe64Val and the described but not functionally assessed variant Leu12Val), using a simplified, fast isoelectric focusing (IEF) approach. After validating the system with known TTR variants, we assessed the sera of five patients carrying these new TTR variants in a heterozygous state. All three variants showed aberrant banding patterns that were similar to those of other well-characterized TTR variants, including the common Val30Met variant that causes ATTR amyloidosis. In addition to a clear band corresponding to monomeric wild-type TTR, we observed an additional variant band at the cathodal side of the IEF gel. These results indicate conformational instability of the new Thr40Asn, Phe64Val and Leu12Val variants. Together with the clinical and immunohistological data of these patients and affected family members, as well as the absence of these variants in human genetic mutation databases, our results strongly hint that these variants are amyloidogenic and therefore probably disease-associated. These findings have implications for patient therapy and for genetic counselling of family members.
Gesehen am 11.12.2019